If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 18 + 4x = -2x Reorder the terms: 18 + 2x + 4x = -2x Combine like terms: 2x + 4x = 6x 18 + 6x = -2x Solving 18 + 6x = -2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2x' to each side of the equation. 18 + 6x + 2x = -2x + 2x Combine like terms: 6x + 2x = 8x 18 + 8x = -2x + 2x Combine like terms: -2x + 2x = 0 18 + 8x = 0 Add '-18' to each side of the equation. 18 + -18 + 8x = 0 + -18 Combine like terms: 18 + -18 = 0 0 + 8x = 0 + -18 8x = 0 + -18 Combine like terms: 0 + -18 = -18 8x = -18 Divide each side by '8'. x = -2.25 Simplifying x = -2.25
| 8w+4(7w+1)= | | (.75)+x(.25)=69.5 | | 4y-2+y+26=6y+30-4y | | 9(5x-8)-44x=3 | | -3y(4x^2-7y)= | | -20x^2+23x+21=0 | | (4x-7)2=-25 | | F(5)=11-2X-3 | | 3(8+4k)+8= | | 4x+5x-5=22 | | 5x+12-2=55 | | 12621-9097= | | -17-4m=-(m-4) | | x(3+5)-4=76 | | 4x^2-26x-46=0 | | x(3+5-4)=76 | | log(4)(5+2x)=2 | | -12x-6(6)=9 | | 72-2x=12-8x | | -61-5x=47-11x | | 2-5(5r+7)=3-7r | | 6(c-3)=7(c-4) | | -5.2+9=-a | | 11x-10=15+10x | | 27.375=b+19.125 | | 6(v-5)=v-15 | | y-36=-18 | | 125t=85(t+3) | | -x-8-3x=-16 | | t^3+t^2-2t-1=0 | | Log[4](5+2x)=2 | | -42+7x=3x+58 |